Oropharyngeal dysphagia in neonates; prevalence and risk factors within a South African context - Porter, Kirsten (Department of Pathology, 2025)
Background: The prevalence of neonatal oropharyngeal dysphagia (OPD) remains largely unexplored in lower middle-income countries, with limited published research on this topic. In the South African context, factors such as poverty, burden of disease and limited access to healthcare may elevate the risk of OPD among neonates. Improvements in neonatal medical care have led to higher survival rates for neonates with complex medical conditions yet also increased the likelihood of feeding and swallowing difficulties. Contextual information on the prevalence, nature and risk factors for OPD is important for healthcare planning and optimal service delivery. Research aim and objectives: To describe OPD and the associated risk factors in neonates admitted into a neonatal unit in South Africa. The objectives of this research study were to describe the prevalence, nature and risk factors associated with OPD in neonates, including medical conditions, gestational age and birthweight. Method: A prospective, descriptive cross-sectional study design was used to describe OPD and the associated risk factors in 160 (N=160) neonates, 34 weeks or older, who were admitted into a neonatal intensive care unit (NICU) and were considered medically stable. Feeding and swallowing was assessed using a reliable and validated tool, the Neonatal Feeding Assessment Tool (NFAS), which allowed for the description of the nature of OPD. The prevalence of OPD and associations between OPD and various risk factors were analysed statistically. Results: Thirty-two participants (20%; n=32) were diagnosed with OPD according to the NFAS criteria, although more participants (43.1%; n=69) presented with some clinical signs of OPD. More than 80% of neonates with OPD were born premature (n=26; 81.3%) and/or with a low birthweight (n=28; 87.5%), while respiratory (n=23; 71.9%) and neurologic (n=9; 28.1%) complications were the most prevalent medical conditions reported in neonates with OPD in this study. Neonates born premature and/or with a low birthweight as well as those with medical conditions (neurologic, cardiorespiratory, anatomic, genetic and gastrointestinal) were at increased risk for OPD (OR>1.00). A statistically significant association between neonates with gastrointestinal complications and OPD was found (p=0.045). Neonates with OPD presented with suboptimal physiologic functioning (n=27; 84.9%), inadequate state of alertness (n=30; 94%) and stress cues during feeding (n=28; 87.5%). Nearly all neonates with OPD had non-nutritive (n=31; 96.9%) and nutritive suck (n=32; 100%) difficulties and over two-thirds of neonates with OPD presented with signs typical of OPD such as weak and/or delayed initiation of suck, coughing and poor lip closure leading to spillage during feeding. Conclusion: One in five neonates admitted to the neonatal unit presented with OPD, even once medically stable and over 34 weeks gestation. Neonates with multiple medical conditions or risk factors were more likely to present with OPD. The results of this study highlight the complexity of OPD in neonates and the need for timeous inclusion of oral feeding protocols in the management of neonates, and the role of speech-language therapists in the assessment and management of neonates at risk for OPD to ensure optimal management.